Human and Object Detection and Interaction Analysis in Video Image Processing - Mohd Zubir, Azhana (IRC, 2019)
Interaction analysis between human and objects are a part of video image processing. Human and object interactions contain an important data that can be extracted and analyzed. In order to understand the motive and purpose of object motion and the reason they occur, interaction analysis between human and objects should be carried out. This will give us an understanding of human behavior. From a video sequence, the human and objects and their motions are detected through an algorithm process. These motions are then analyzed as interactions when the human and objects overlaps each other. From this research, the interactions of the human and objects and its surrounding will result in having either interaction or no interaction at all. Accuracy of the human and object detection is critical to this analysis. It may be used in various scenes especially surveillance camera system, for eliminating threatening conditions such as robbery or theft in a shop